2012
DOI: 10.1542/peds.2012-0310
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast for Children With Obstructive Sleep Apnea: A Double-blind, Placebo-Controlled Study

Abstract: A 12-week treatment with daily, oral montelukast effectively reduced the severity of OSA and the magnitude of the underlying adenoidal hypertrophy in children with nonsevere OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 26 publications
4
133
0
4
Order By: Relevance
“…Efficacy against OSAHS has been harder to show, probably because the The importance of leukotrienes in adenoid and tonsillar inflammation was suggested by an increase in leukotriene concentration and in the number of adenoid and tonsillar leukotriene receptors in children with OSAHS compared to rates in lymphoid tissue in children with iterative pharyngitis 4 . Antileukotrienes proved effective in childhood OSAHS in a randomized double-blind placebo-controlled study of 2 groups of 23 children each 5 ; only the antileukotriene group showed radiologic regression of adenoid hypertrophy and reduced AHI.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…Efficacy against OSAHS has been harder to show, probably because the The importance of leukotrienes in adenoid and tonsillar inflammation was suggested by an increase in leukotriene concentration and in the number of adenoid and tonsillar leukotriene receptors in children with OSAHS compared to rates in lymphoid tissue in children with iterative pharyngitis 4 . Antileukotrienes proved effective in childhood OSAHS in a randomized double-blind placebo-controlled study of 2 groups of 23 children each 5 ; only the antileukotriene group showed radiologic regression of adenoid hypertrophy and reduced AHI.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…While it has been suggested that such data justifies the use of intranasal steroids in otherwise healthy children with mild to moderate OSA, which subgroup of patients will benefit most, the optimal dosage, and optimal duration of therapy are still unclear. Likewise, the use of a different medication to modify leukotriene-mediated inflammation, montelukast, has also been reported to improve tissues size and respiratory indices in milder pediatric OSA in an open-label 16 week trial [43]. In a recent double-blind, placebo controlled study of montelukast in 46 children with PSG-confirmed OSA, significant improvements were reported at 12 week follow up in polysomnography (obstructive apnea index), symptoms, and adenoid size (measured by lateral neck radiograph) [44].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%
“…Central nervous system stimulants have been the drugs most widely used in the treatment of sleepiness in narcolepsy, and amphetamines were first proposed in 1935 [43]. The use of methylphenidate was later encouraged because of a shorter half-life and lower incidence of side effects.…”
Section: Narcolepsymentioning
confidence: 99%
“…Leukotrienes are inflammatory mediators found in the respiratory system and these play a role in several allergic childhood diseases (5). Cysteinyl leukotriene receptor-1 mediates the inflammatory pathway and has been found in high rates in postoperative adenotonsillar tissues in pediatric patients with obstructive sleep apnea (6)(7)(8).…”
mentioning
confidence: 99%
“…It is used to inhibit the inflammatory component in the disease group, which is triggered by allergic reactions (5).…”
mentioning
confidence: 99%